PENYULUHAN UNTUK MENINGKATKAN PENGETAHUAN DUKUN BAYI TENTANG PERAWATAN MASA NIFAS - Agustina Nugrahwati; Septerina Purwandani Winarso; Fajaria Nur Aini (Jurnal Sains Kebidanan, 2020)
Postpartum mothers and many families who use the services of a traditional birth attendants to carry out postnatal care, because the cost is cheaper, and this is the habit of society in their generations. Because postpartum care is very important to be done properly, the practice of the traditional birth attendants is also required to get the attention of midwives, because the knowledge and skills the traditional birth attendants are not a systematic formal education. The aim of this study is to determine the effectiveness of education’s method to increased knowledge of the traditional birth attendants knowledge about postpartum care. This research is a quasi-experimental study. The study designed use a one group pretest posttest with control group design. The population of this study is the traditional birth attendants, the sample in this study was total sampling, with a total of 15 treatment groups, and 15 control groups. Statistical test results using the Wilcoxon test p-value 0.035 (p 0.005) so that it can be concluded that counseling with the lecture method is effective in increasing the level of knowledge of the traditional birth attendants about postpartum care.